Healthcare Workers' Knowledge and Attitude Towards COVID-19 and Its Effect on Their Mental Health in England - Ayeni, Ifedayo Eunice; Kainesie , John; Sivasubramanian , Madhini (Asian Journal of Public Health and Nursing, 2024)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious disease that is presently a global public health concern. Evidence from previous disease outbreaks, along with early evidence from the COVID-19 pandemic, suggests that these events have significant short and long-term effects on the mental health of healthcare workers. All healthcare stakeholders should create short and long-term plans to support the mental health of workers during and after the COVID-19 pandemic. This research examines the knowledge and attitude of healthcare workers towards the COVID-19 crisis, investigates the impact on their mental health. Methods: The study used a cross-sectional quantitative design with a closed ended structured anonymous questionnaire as a tool to explore data online from healthcare workers at the study site in selected hospitals in England. The quantitative data analysis software SPSS was used to analyse the data using inferential statistics and cross tabulation. Results: Data from this quantitative study was collected using a questionnaire and analysed using SPSS and inferential statistics. Findings show that 80% of the respondents significantly have general good knowledge of COVID-19 and 11% had moderate and poor knowledge respectively. A good attitude towards COVID-19 was found among 73% of respondents while a poor attitude among 27%. An increase in death rate (10.9%), close contact with the patient (10.9%), and getting infected thereby transmitting the virus to family were most of the factors linked to the effect on their mental health. Accepting responsibility (9.9%), escaping evidence to relieve stress (9.7%), and calling a friend (9.6%) were methods adopted by the respondents as a coping strategy. Conclusion: Healthcare workers’ mental well-being has been negatively affected by the COVID-19 pandemic, resulting in depression, anxiety, and stress. It is recommended that healthcare authorities ensure that they provide necessary assistance, proper information, and training and substantiate practical resources. Self-care is one of the important needs during mental disorders thus it is recommended that healthcare workers should focus on taking time out to mentally relax themselves during work.